2005
DOI: 10.1177/1744629505056695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of teacher training in Applied Behaviour Analysis

Abstract: Interventions for children with autism based upon Applied Behaviour Analysis (ABA) has been repeatedly shown to be related both to educational gains and to reductions in challenging behaviours. However, to date, comprehensive training in ABA for teachers and others have been limited. Over 7 months, 11 teachers undertook 90 hours of classroom instruction and supervision in ABA. Each teacher conducted a comprehensive functional assessment and designed a behaviour support plan targeting one behaviour for one chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
3
41
0
2
Order By: Relevance
“…This project strengthens and extends findings by Grey et al (2005) in several ways. First, the students learned scientist-practitioner skills that produced important behaviour changes in the children under their care.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This project strengthens and extends findings by Grey et al (2005) in several ways. First, the students learned scientist-practitioner skills that produced important behaviour changes in the children under their care.…”
Section: Discussionsupporting
confidence: 82%
“…Structured evaluation The eighteen students who completed the course filled in the Teacher Evaluation Instrument (modified version of Grey et al, 2005), based on 13 items in which responses were made on a scale of 1 = less than expected to 5 = greater than expected. In response to all item student ratings, the mean for 12 of the items was a 4 or above; the median for five of the items was 5, and for the remaining eight was 4.…”
Section: Teacher Responsesmentioning
confidence: 99%
“…A potential solution to this problem is the use of single case methodology whereby each participant effecitively operates as their own control by the use of baseline recording. Though normally used in a single participant fashion, previous studies have combined single case data into a group format whereby it is possible to determine degree of change from baseline to intervention conditions across at both the individual and group level [8]. The current study adopts this strategy and attempts to evaluate the application of behaviour change techniques by medical students to a pre identified and self-selected health behaviour by comparing baseline data with intervention data.…”
Section: Introductionmentioning
confidence: 99%
“…Learning a new theory does not, however, come without its challenges. A study done by Grey, Honan, McClean, and Daly (2005) noted that although teachers were initially adverse to ABA, towards the end of the training they reported that the use of functional analysis is highly beneficial and believed that systematic instruction could really effect change. This modification in attitude was empowering teachers to face challenging behavior (Grey et aI.).…”
Section: )mentioning
confidence: 99%
“…For example, Grey, Honan, McClean, and Daly (2005) evaluated ABA for teacher training. A total of eleven special needs teachers completed a training course in ABA.…”
Section: Best Practice Techniques For Autismmentioning
confidence: 99%